Business process management workshops : BPM 2018 International Workshops, Sydney, NSW, Australia, September 9-14, 2018, Revised papers /: BPM 2018 International Workshops, Sydney, NSW, Australia, September 9-14, 2018, Revised papers. (2019) - Unknown
No abstract available